Optimization of Digital Marketing Strategies to Increase Engagement on Social Media at MNC Securities Surabaya Branch - Dewi, Aulia Friya Rahana; Nugroho, Rusdi Hidayat (CV. Lenggogeni Data Publishing, 2025)
Digital marketing has become an important element in the modern business world, including in the financial services sector, such as securities. This research aims to evaluate and optimize digital marketing strategies on the Instagram account of MNC Sekuritas Surabaya Branch for 2024 in order to increase audience engagement. With a qualitative approach, data were collected through interviews, social media analysis, and direct observation. The research results show that the use of educational, interactive, visually appealing content, as well as the optimal utilization of social media platform algorithms, can increase audience engagement levels. This concludes that the implementation of integrated and data-driven digital marketing strategies is crucial for building strong relationships with the audience.